Validation of Cost-Effective Data Acquisition System on Motorcycle - Saipul Bahri, Muhammad Amin (Progress in Engineering Application and Technology, 2022)
A data acquisition system (DAQ) is a combination of software and hardware that makes it possible to measure or control the physical properties of anything in the real world. Unfortunately, the compact DAQ, which is most often used, is too expensive for preliminary study, such as for motorcycle dynamic study. The objective of this study is to study the four degrees of freedom (4-DOF) motion on a motorcycle. To develop cost-effective data acquisition systems using Arduino and to validate the data from the DAQ using actual motorcycle ride motion. In order to detect the vertical motion of sprung and unsprung masses that are taken into consideration, a gyroscope is placed on two separate sections of the vehicle, which are made up of a Yamaha 135 LC chassis and a lower arm. Gyro sensor is being used to gather data on the body’s vertical acceleration and vertical motion. The experiment will be carried out at vehicle speeds of 25 km/h for the slalom test. For the bump test, the speed of the motorcycle is 20 and 30 km/h, and for the braking test, the speed of the motorcycle is 20 and 25 km/h. Arduino IDE is used to transmit data from a sensor to a laptop. Generally, as the pattern of slalom tests generated in this study is nearly the same as in the previous study, it can be assumed the experiment is validated, although there is some discrepancy in the peak of roll and yaw rate. The DAQ on motorcycle was validated by comparing with simulation method. In the result, the higher peak of roll and yaw rate is around 40°/s, which may be expected because the rider’s speed is less than 5 km/h but the pattern is still the same as in the previous study and the study continued with braking and bump tests.